Lower extremity fracture prevention and management in persons with spinal cord injuries and disorders: The patient perspective. (2nd November 2022) - Etingen, Bella; Carbone, Laura D.; Guihan, Marylou; Ray, Cara; Aslam, Hamad; Elam, Rachel; Weaver, Frances M.
Abstract : Context/Objective: To describe patient experiences with fracture prevention and management among persons with spinal cord injuries/disorders (SCI/D). Design: Qualitative data collected via semi-structured telephone interviews. Setting: Veterans Health Administration (VA) SCI/D System of Care. Participants: Veterans with SCI/D ( n = 32) who had experienced at least one lower-extremity fracture in the prior 18 months. Interventions: N/A. Outcome Measures: Interview questions addressed patients': pre-fracture knowledge of osteoporosis and bone health, diagnosis and management of osteoporosis, history and experiences with fracture treatment, and post-fracture care and experiences. Results: Participants expressed concerns about bone health and fractures in particular, which for some, limited activities and participation. Participants recalled receiving little information from providers about bone health or osteoporosis and described little knowledge about osteoporosis prevention prior to their fracture. Few participants reported medication management for osteoporosis, however many reported receiving radiographs/scans to confirm a fracture and most reported being managed non-operatively. Some reported preference for surgical treatment and believed their outcomes would have been better had their fracture been managed differently. Many reported not feeling fully included in treatment decision-making. Some described decreased function, independence and/or participation post-fracture. Conclusion(s): Our results indicate that persons with SCI/D report lacking substantive knowledge about bone health and/or fracture prevention, and following fracture, feel unable and/or hesitant to resume pre-fracture participation. In addition, our findings indicate that individuals with SCI/D may not feel as engaged as they would like to be in establishing fracture treatment plans. As such, persons with SCI/D may benefit from ongoing discussions with providers about risks and benefits of fracture treatment options and consideration of subsequent function and participation, to ensure patients preferences are considered.